1999
DOI: 10.1111/j.1572-0241.1999.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaky Gut in Alcoholic Cirrhosis: A Possible Mechanism for Alcohol-Induced Liver Damage

Abstract: Because only the alcoholics with chronic liver disease had increased intestinal permeability, we conclude that a "leaky" gut may be a necessary cofactor for the development of chronic liver injury in heavy drinkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(67 citation statements)
references
References 33 publications
1
65
1
Order By: Relevance
“…This in turn can lead to alcoholic cirrhosis and liver failure, which is a causal factor in the development of alcoholic endotoxemia and hepatitis. Keshavarizian [3] found that intestinal barrier dysfunction was observed in alcoholics who also had liver disease. The intestinal barrier is formed by the epithelial cells and the tight junctions (TJs) between them [4], and provides barrier functions between luminal triggers and the host.…”
Section: Introductionmentioning
confidence: 99%
“…This in turn can lead to alcoholic cirrhosis and liver failure, which is a causal factor in the development of alcoholic endotoxemia and hepatitis. Keshavarizian [3] found that intestinal barrier dysfunction was observed in alcoholics who also had liver disease. The intestinal barrier is formed by the epithelial cells and the tight junctions (TJs) between them [4], and provides barrier functions between luminal triggers and the host.…”
Section: Introductionmentioning
confidence: 99%
“…In many patients this abnormality persisted for up to 2 weeks after cessation of drinking [25]. Alcoholics with chronic liver disease showed a markedly increased intestinal permeability by the L/M test, whereas the increase in intestinal permeability was slight in alcoholics with no liver disease [26]. Only patients with increased intestinal permeability had an altered fecal microbiota composition: a drastic decrease in the abundance of Ruminococcus , Faecalibacterium , Subdoligranulum , Oscillibacter , and Anaerofilum belonging to the Ruminococcaceae family [27].…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%
“…[11][12][13][14][15] Bacteria deconjugate bile acids, 16 and bacterial deconjugation should result in a further reduction in bile acid concentration because unconjugated bile acids are rapidly absorbed by nonionic diffusion. Finally, studies have indicated there is increased small intestinal permeability in cirrhosis, [17][18][19][20] raising the possibility that even conjugated bile acids, which are membrane-impermeable in health, might be absorbed passively. In principle, the combination of decreased conjugated bile acid secretion, increased deconjugation, and passive permeation of conjugated bile acids should lead to a marked decrease in the intraluminal concentration of bile acids.…”
mentioning
confidence: 99%